Manajemen Risiko Kepatuhan Syariah dalam Lembaga Keuangan Syariah - Hasnah Haron; M. Sholeh Wafie; Salsabila Firdaus (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Sharia compliance is a key pillar in the operations of Islamic financial institutions, which continues to grow along with the development of the global Islamic financial industry. Sharia compliance risk management is a crucial factor in protecting institutions from the risk of non-compliance, which can seriously impact business sustainability, reputation, and consumer trust. This article discusses critical aspects of Sharia compliance risk management, including (A) definitions and basic principles, (B) risk identification and evaluation, (C) mitigation strategies, and (D) the application of technology in risk management. Case studies and practical examples are presented to provide a concrete picture of the challenges and solutions faced by Islamic financial institutions. With a comprehensive approach, this article is expected to provide insight into the importance of Sharia compliance risk management in maintaining the integrity and stability of Islamic financial institutions in the global market.